Aplicação web de gerenciamento de mensagens - Costa, Mateus Fernando Goetens da (2024)
With the aim of putting into practice all the learning obtained during the Internet System Technology course, a web application was developed for managing the sending of messages called AwGem. AwGem is a web application that allows the user to register a message and make it available to be sent by email, SMS and/or WhatsApp, enabling the same message to be sent to one or more users, and also leaving the user in control of the shipments. This application was developed using the Laravel framework, which is built using the PHP programming language, and the MySql relational database is used. Laravel uses the MVC architecture pattern, separating the application into three parts that interact with each other, increasing code reuse and maintenance capabilities. This application will integrate with Gmail to send emails and also perform integration with the Twilio platform to send WhatsApp and SMS messages.